LOW COST ALTERNATIVE SOLAR COLLECTOR WITH ABSORPTION SURFACE FORMED BY PVC TUBES - Souza, L. G. M.; Santos, R. D.; L. Neto, H. J. (Revista de Engenharia Térmica, 2007)
A no conventional new model of solar collector is presented, composed for multiple units of PVC tubes in parallel to absorb solar radiation, through a new model of linking between same and the pipes of admission and water exit. The collector’s box is made with a composite of matrix ceramic and coated with resin, propitiating the elimination of the thermal isolation, usually glass wool. The collector is composed of only three elements: the box, the absorb grid and glass. It will board constructive aspects, demonstrating the easiness to manufacture such archetype that is characterized for presenting a cost of manufacture sufficiently reduced. It will be presented values of thermal parameters of the collectors, working in regimen of thermosiphon in a volume of water in the order of 250 liters (66.03 gallons). One will demonstrate the thermal, economic and the materials viability of this collector, enabling it to serve as another option to the conventional systems of market heating, mainly to the attainment of low temperatures.